2019
DOI: 10.1155/2019/3652894
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Vitamin D Deficiency Predicts Mortality in Ischemic Stroke Patients

Abstract: Background. Vitamin D (VD) deficiency is considered an independent risk factor for death due to cardiovascular events including ischemic stroke (IS). We assessed the hypothesis that decreased levels of 25-hydroxyvitamin D (25-OH-D) are associated with increased risk of mortality in patients with IS. Methods. Serum 25-OH-D, intact parathyroid hormone (iPTH), and intact fibroblast growth factor 23 (iFGF23) levels were assessed in serum of 240 consecutive patients admitted within the 24 hours after the onset of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 31 publications
5
27
0
Order By: Relevance
“…In this study, the results of multivariable logistic regression analysis showed that after controlling other risk factors, age, dyslipidemia, vitamin D deficiency, and large infarction size were statistically significant independent factors associated with stroke severity. This was in agreement with other studies which showed that vitamin D deficiency was associated with stroke severity [25,33] Regarding stroke outcome, multivariable logistic regression analysis showed that high NIHSS score, vitamin D deficiency, and large infarction size were significantly associated with mRS. Our result was in accordance with the result of other studies demonstrated that vitamin D level is a good biomarker for prognosis, functional outcome, and death in patients with acute ischemic and hemorrhagic stroke [25,26,33,34]. This could be explained by the neuroprotection role of vitamin D via activation of detoxification pathways, upregulation of antioxidation/anti-inflammatory mechanisms, inhibition of inducible nitric oxide synthase, and regulation of neuronal calcium metabolism [35,36].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the results of multivariable logistic regression analysis showed that after controlling other risk factors, age, dyslipidemia, vitamin D deficiency, and large infarction size were statistically significant independent factors associated with stroke severity. This was in agreement with other studies which showed that vitamin D deficiency was associated with stroke severity [25,33] Regarding stroke outcome, multivariable logistic regression analysis showed that high NIHSS score, vitamin D deficiency, and large infarction size were significantly associated with mRS. Our result was in accordance with the result of other studies demonstrated that vitamin D level is a good biomarker for prognosis, functional outcome, and death in patients with acute ischemic and hemorrhagic stroke [25,26,33,34]. This could be explained by the neuroprotection role of vitamin D via activation of detoxification pathways, upregulation of antioxidation/anti-inflammatory mechanisms, inhibition of inducible nitric oxide synthase, and regulation of neuronal calcium metabolism [35,36].…”
Section: Discussionsupporting
confidence: 92%
“…These results were in agreement with the results obtained by other studies [23][24][25][26]. The association of vitamin D deficiency with stroke severity and outcome after controlling for other risk factors suggests a role for vitamin D in the pathogenesis of [27,28].…”
Section: Discussionsupporting
confidence: 92%
“…Another study from Poland evaluated vitamin D levels and mortality in 240 patients after diagnosing ischemic stroke. This study showed that in patients with ischemic stroke, only 1.3% had optimal levels of vitamin D of higher than 30 ng/mL and during the 45-month follow-up, the patients with severe deficiency, defined as levels lower than 10 ng/mL, had a much higher and statistically significant mortality rate per year: 4.81% compared with 1.89% in patients without severe deficiency [ 93 ]. Thus, severe vitamin D deficiency is a significant factor that increases death risk in patients with ischemic stroke.…”
Section: Clinical Studies On Atherosclerosis and Vitamin D Deficiementioning
confidence: 99%
“…It is noteworthy that a meta-analysis of pooled data from 32 studies recently found that serum 25(OH)D concentrations < 30 ng/mL were associated with higher all-cause mortality than concentrations > 30 ng/mL [119]. Specifically, despite some conflicting results, there is evidence that low solar UVB exposure and low serum 25(OH)D levels are associated with an increased risk of CVD, as well as that CVD mortality is about double in older individuals with deficient 25(OH)D concentrations compared with age-matched individuals with adequate 25(OH)D concentrations (> 30 ng/mL) [120][121][122][123][124]. Indeed, accumulating evidence suggests that vitamin D insufficiency or deficiency may adversely affect the cardiovascular system through multiple effects.…”
Section: Vitamin D Deficiency and Its Impact On Cerebrovascular Diseasesmentioning
confidence: 99%